Cofilin determines the migration behavior and turning frequency of metastatic cancer cells - Sidani, Mazen (The Rockefeller University Press, 2007)
We have investigated the effects of inhibiting the expression of cofilin to understand its role in protrusion dynamics in metastatic tumor cells, in particular. We show that the suppression of cofilin expression in MTLn3 cells (an apolar randomly moving amoeboid metastatic tumor cell) caused them to extend protrusions from only one pole, elongate, and move rectilinearly. This remarkable transformation was correlated with slower extension of fewer, more stable lamellipodia leading to a reduced turning frequency. Hence, the loss of cofilin caused an amoeboid tumor cell to assume a mesenchymal-type mode of movement. These phenotypes were correlated with the loss of uniform chemotactic sensitivity of the cell surface to EGF stimulation, demonstrating that to chemotax efficiently, a cell must be able to respond to chemotactic stimulation at any region on its surface. The changes in cell shape, directional migration, and turning frequency were related to the re-localization of Arp2/3 complex to one pole of the cell upon suppression of cofilin expression.